Analisis Determinan Perdagangan Intra-Industri Indonesia Dengan 5 Mitra Dagang Di Kawasan Asean (Analisis Data Panel Tahun 2015 2023) - Aulia, Zahara; Kurniawan, Muhammad; Nurmalia, Gustika (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
In general, intra-industry trade is trade or exchange of similar goods involving two or more countries. This study aims to analyze the effect of exchange rates (CURS), gross domestic product (GDP), and foreign investment (FDI) on Indonesia's intra-industry trade with 5 trading partner countries in the ASEAN region. This study uses panel data from 5 ASEAN countries (Singapore, Malaysia, Thailand, Vietnam, Philippines) with a purposive sampling method. This type of research uses a quantitative approach, obtained from secondary sources and data analysis using the Eviews10 tool. The results of the study show. The exchange rate has a positive and significant effect on Indonesia's Intra-industry Trade. GDP has a negative and significant effect on Indonesia's Intra-industry Trade. FDI has a positive and insignificant effect on Indonesia's Intra-industry Trade. Exchange Rate, Gross Domestic Product (GDP), Foreign Investment (FDI) simultaneously affect Indonesia's Intra-industry Trade.